Pendidikan Politik Pembangunan: Telaah Rezim Sustainable Development Goals (SDGs) pada Calon Aparatur Pemerintah (Praja IPDN Kampus NTB) - Alfian Hidayat; Purnama Safitri (Jurnal Pengabdian Pada Masyarakat, 2020)
DEVELOPMENT POLITICAL EDUCATION: REGIME REVIEW OF THE SUSTAINABLE DEVELOPMENT GOALS (SDGS) TO PROSPECTIVE GOVERNMENT APPARATUS (CADET IPDN OF NTB CAMPUS). The service activity is intended to provide insight and insight to prospective state apparatuses (IPDN cadets) regarding the strategy of implementing SDG’s (Sustainable Development Goals) for 3 development sectors namely socioeconomic and environmental. In 2015 a global agreement on development was formulated at the United Nations Sustainable Development Summit with 17 global development goals. In realizing Sustainable Development in the midst of globalization and regionalization, demands a proactive local government and has a strategy in establishing partnerships in the form of international cooperation. The success of achieving the SDGs will depend on an inclusive global partnership with active involvement from both central and regional governments (cities/districts/provinces) with civil society, the private sector, philanthropic institutions, academics and UN agencies. This dedication activity provides a deepening of SDGs in the social aspect by emphasizing the issue of gender equality, then in the economic aspect emphasizing the issue of economic growth and innovation (through the Global Value Chain approach), finally the environmental aspects emphasizing the issue of climate change. The method of this activity is carried out with a workshop model by giving material in class.